2012
DOI: 10.1180/claymin.2012.047.3.05
|View full text |Cite
|
Sign up to set email alerts
|

A simple approach for producing high aspect ratio fluorohectorite nanoplatelets utilizing a stirred media mill (ball mill)

Abstract: The potential of platy nanofillers like clays in polymer nanocomposites is mostly determined by their aspect ratio. The degree of improvement that may be achieved in respect to reinforcement, gas-barrier properties and flame retardancy critically depends on the aspect ratio. Thus, increasing the aspect ratio is highly desirable in order to explore the full potential of the clay filler. Mechanical shear stress as generated in the grinding chamber of a stirred media mill (ball mill) induced an efficient exfoliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…with Mg 2? cations in an aqueous suspension [16][17][18]. This Mg-hect with its highly hydrated state in an aqueous dispersion was processed in a stirred media mill in order to exfoliate the nanofiller tactoids by applying mechanical shear forces.…”
Section: Maximization Of Aspect Ratio and Rendering The Stiffness Statementioning
confidence: 99%
See 2 more Smart Citations
“…with Mg 2? cations in an aqueous suspension [16][17][18]. This Mg-hect with its highly hydrated state in an aqueous dispersion was processed in a stirred media mill in order to exfoliate the nanofiller tactoids by applying mechanical shear forces.…”
Section: Maximization Of Aspect Ratio and Rendering The Stiffness Statementioning
confidence: 99%
“…This Mg-hect with its highly hydrated state in an aqueous dispersion was processed in a stirred media mill in order to exfoliate the nanofiller tactoids by applying mechanical shear forces. After milling, the typical tactoid thickness was found to be (10-15 nm) [18]. As a first approximation of the lateral extension, the hydrodynamic radius obtained from SLS is used [20].…”
Section: Maximization Of Aspect Ratio and Rendering The Stiffness Statementioning
confidence: 99%
See 1 more Smart Citation
“…Planetary ball mills are widely used for clay powder preparation, however very few studies investigating the use of stirred ball/bead mills under wet conditions to carry out size reduction on clay nanoparticles have been reported, nor have they considered the commercial necessity of scalability. (Ziadeh et al, 2012). Most of the above mentioned studies used microscopy techniques to characterise the size reduction or the morphological changes, but no effective methods are reported to observe the exfoliated layers and thin platelets due to the agglomerates or clumps, which brings limitations to the accurate measurement of the reduced particle size.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 96%
“…The temperature of maximum dehydroxylation and the weight loss in the temperature range corresponding to dehydroxylation both showed a linear relationship with decreasing structural order along the c* direction (crystallite thickness) of phyllosilicates after progressive less intensive grinding (Dellisanti and Valdrè, 2008). Ziadeh et al (2012) demonstrated the ability of ball grinding to increase the aspect ratio (crystallite a-b plane dimension over the c* dimension) of synthetic fluorohectorites.…”
Section: Introductionmentioning
confidence: 92%